FEATURES OF THE SWEDISH MODEL OF SOCIO-ECONOMIC DEVELOPMENT AND PERSPECTIVES OF APPLICATION FOR UKRAINE - PANOVA, Iryna; ILYUSHCHENKO, Igor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the peculiarities of the Swedish model of socio-economic development and the prospects for their application to Ukraine. It is noted that today Sweden is one of the leading countries in the world with a high standard of living and an efficient economy. It is argued that the study of the Swedish model allows for a deeper understanding of the principles which ensure its success. It is highlighted that a number of countries are interested in analyzing and adapting the Swedish experience to improve their own socio-economic systems. The modern Swedish model is an important example for countries with different economic and political conditions. In the context of changes in the global economy, demographic shifts and other challenges, the question of the sustainability and effectiveness of the Swedish model arises. The article analyzes the social dimension of the Swedish economic model, characterizes the economic aspects of the Swedish model, and assesses the prospects of applying the Swedish development model for Ukraine. The object of the study is the Swedish model of socio-economic development. The subject of the study is the Swedish experience and its possible application to Ukraine. The purpose of this paper is to provide a scientific and theoretical analysis of the process of formation and evolution of the Swedish model of socio-economic development, as well as to determine the prospects for its adaptation for Ukraine. Thus, further research of the Swedish economic model will help to identify its strengths and possible weaknesses. A comprehensive study of the historical aspects of Swedish social policy, innovative approaches to governance, and principles of environmental sustainability can form the basis for developing strategic recommendations that would contribute to Ukraine’s development. A comparative analysis with other models of socio-economic development will help to determine which elements of the Swedish model can be effectively adapted and integrated into different contexts, ensuring harmonious and sustainable development of both the state and society.